Dancing a Nation: Philippine Contemporary Dance and Narratives of the Nation - Pison, Ruth Jordana Luna (Philippine Humanities Review, 2015)
So much has been written about the nation vis-à-vis other fields in the humanities, literature in particular. My interest in dance lies in its peculiar location within and vis-à-vis the discourse of the nation. An ephemeral form, dance has elicited various, and even contradictory, valuations; most of the time it is considered a mere form of entertainment. It is undeniable, though, that dance has articulated and informed our ideas of the nation and nationhood. In this paper, I explore how three contemporary dance companies based in Quezon City (The University of the Philippines Dance Company, Airdance, and Dance Forum) have rendered their imaginings of the Philippine nation. I focus on Philippine contemporary dance because as a cultural practice, I believe that it has choreographed the many trajectories and issues embodied in the Philippines’s imagining of itself. A number of choreographies by the three companies mobilize motifs, forms, structures, and styles that constitute and signify the Philippine nation; they have, in effect imagined a “national identity.” It is my hypothesis that Philippine contemporary dance offers a space within which the narrative of the nation, one which is different from that deployed by the state, is created. Such space opened by contemporary dance in the country has been selflessly offered by talented choreographers who have, despite meager state support, been persistently creating works under formidable conditions. These contemporary dance choreographers have fleshed out a vision and philosophy of dance rooted in Philippine realities. Keywords: contemporary dance, culture, choreography, Dance Forum, UP Dance Company, Airdance